NASCIDOS NO SILÊNCIO: AS RELAÇÕES ENTRE FILHOS OUVINTES E PAIS SURDOS NA EDUCAÇÃO - Pereira, Osmar Roberto (2012)
This paper seeks to present the experiences of three listeners, besides the author, childrens of deaf parents, discussing family relationships between parents and children, showing the differences in relation to families who have no deaf people at its core, demystifying prejudices and pre -concepts. Due to communication barriers and prejudice, many deaf people ended up being deprived of the right to be parents. In the reports presented in this thesis, there were times when it almost happened in the lives of the subjects interviewed for this research, but with strength and awareness of rights they had, these deaf parents would not allow such a thing to happen. The text begins with the history and formation of the author to then bring the authors covering topics such as deafness (Wrigley, 1996; Lacerda, 1998; Perlin, 1998; Moura, 2000; Sá, 2002; Quadros, 2004; Sacks, 2007), anthropology (Hall, 1992; Gomes, 2008), family relationships (Lacan, 1987) and autobiography (Ferraroti, 1991; Pineau, 2006; Demartini, 2008). The sign language of the deaf and educational history are also discussed in this paper. At the end are presented reports of life history made in the research field of literary form, with analyzes of testimonies collected by interviewees (deaf parents and hearing children) which showed to be son of deaf parents can be as normal as being the child of hearing parents.